Reconnaissance de la profession de Conservateur-Restaurateur : l’expérience belge - Michaël Van Gompen (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Since its creation in 1991, the Belgian association of Conservator-Restorers has endlessly tried to get a better legal recognition for our profession.  The complexity of the process to get the professional exercise properly regulated leaded us to try another way when a new law came into force in 2006.  The new possibility to regulate solely the use of the professional title seemed an easy and interesting way to achieve a satisfying recognition but it was far from being easy after all.